Yeast at the forefront of research on ageing and age-related diseases - Marques, Maria Belém Sousa Sampaio (2019)
Ageing is a complex and multifactorial process driven by genetic, environmental and stochastic factors that lead to the progressive decline of biological systems. Mechanisms of ageing have been extensively investigated in various model organisms and systems generating fundamental advances. Notably, studies on yeast ageing models have made numerous and relevant contributions to the progress in the field. Different longevity factors and pathways identified in yeast have then been shown to regulate molecular ageing in invertebrate and mammalian models. Currently the best candidates for anti-ageing drugs such as spermidine and resveratrol or anti-ageing interventions such as caloric restriction were first identified and explored in yeast. Yeasts have also been instrumental as models to study the cellular and molecular effects of proteins associated with age-related diseases such as Parkinson's, Huntington's or Alzheimer's diseases. In this chapter, a review of the advances on ageing and age-related diseases research in yeast models will be made. Particular focus will be placed on key longevity factors, ageing hallmarks and interventions that slow ageing, both yeast-specific and those that seem to be conserved in multicellular organisms. Their impact on the pathogenesis of age-related diseases will be also discussed.